Sexual crime against children with disabilities: a nationwide prospective birth cohort-study - Christoffersen, Mogens (International Journal of Population Data Science, 2019)
Background The rate of violent and sexual victimization against children with disabilities is thought to be lower than the rate for children without disabilities but several studies shows otherwise. Aims The study focuses on examining sexual crime against children with disabilities and explaining differences in victimization in order to elucidate to what extent types of disability, family disadvantages, gender, high-risk behavior, location influences adolescents’ risk of sexual victimization. Previous population studies lack scientifically sound research methodology and results are weak or inconclusive. Method data is based on a national study of reported sexual crime against children in Denmark aged between 7 and 18 years of age using total birth cohorts (N=678,000). The statistical analysis is a discrete time Cox-model. An extended list of potential risk factors was included in the analysis in order to adjust for confounding. The potentially confounding risk-factors were collected independently from various population-based registers, e.g. employment statistics, housing statistics, education statistics, income compensation benefits, and population statistics (e.g. gender, age, location). Hospital records with information on types of disability based on the national inpatient register and national psychiatric register were collected independently of the collection of law enforcements records about reported sexual offences under the Danish Central Crime Register. Results Children with disabilities are more likely to be victimized of a reported sexual crime than non-disabled children: ADHD odds ratio: 3.7 (3.5-3.9), mental retardation: 3.8 (3.6-4.0), autism 3.8 (3.6-4.0). Conclusion The present study finds that family disadvantage e.g.parental substance abuse, parental violence, family separation, the child in care, and parental unemployment indicate an increased risk of being a victim of a sexual crime. Assessment of risk factors may permit professionals to facilitate prevention and treatment interventions. The study underreports the size of the problem because adolescents with disabilities face barriers when reporting victimization.